Statics correction methods for 3D converted-wave (PS) seismic reflection. Issue 3 (1st September 2017) - Strong, Shaun; Hearn, Steve
Abstract : One of the most difficult steps in the PS processing sequence is estimation of the S-wave receiver statics. This process is particularly important at the coal scale, due to the need for higher frequency content (better resolution). We present an analysis of three approaches for estimating 3D PS statics. These include a surface-consistent inversion algorithm (analogous to the residual-statics method used in conventional P-wave processing), PPS refraction statics, and a so-called robust statistical method. This analysis is achieved through the use of synthetic models, and a coal-scale 3D-3C survey acquired in the Bowen Basin. The presented datasets demonstrate that the surface-consistent inversion method can become unstable in certain environments. This is likely due to parameter leakage between receiver and structural terms, caused by the highly asymmetric nature of the shallow PS reflection paths. The robust statistical method appears reliable for determination of short-wavelength receiver statics, and hence is useful for continuity enhancement. The PPS refraction approach can provide both short-wavelength and long-wavelength solutions, provided the PPS arrivals can be picked reliably. As with P-wave analysis, a combination of algorithms may provide the most effective production tool for determination of PS receiver statics. Abstract : An analysis of three approaches for estimating 3D PS statics is presented. These include a surface-consistent inversion algorithm, PPS refraction statics, and a robust statistical method. This analysis is achieved through the use of synthetic models, and a coal-scale 3D-3C survey acquired in the Bowen Basin.